The Male Reproductive Toxicity Caused by 2-Naphthylamine Was Related to Testicular Immunity Disorders - Pengyuan Dai; Mengqian Ding; Jingyan Yu; Yuan Gao; Miaomiao Wang; Jie Ling; Shijue Dong; Xiaoning Zhang; Xuhui Zeng; Xiaoli Sun (Toxics, 2024)
2-naphthylamine (NAP) was classified as a group I carcinogen associated with bladder cancer. The daily exposure is mostly from cigarette and E-cigarette smoke. NAP can lead to testicular atrophy and interstitial tissue hyperplasia; however, the outcomes of NAP treatment on spermatogenesis and the associated mechanisms have not been reported. The study aimed to investigate the effect of NAP on spermatogenesis and sperm physiologic functions after being persistently exposed to NAP at 5, 20, and 40 mg/kg for 35 days. We found that sperm motility, progressive motility, sperm average path velocity, and straight-line velocity declined remarkably in the NAP (40 mg/kg) treated group, and the sperm deformation rate rose upon NAP administration. The testis immunity- and lipid metabolism-associated processes were enriched from RNA-sequence profiling. Plvap, Ccr7, Foxn1, Trim29, Sirpb1c, Cfd, and Lpar4 involved in testis immunity and Pnliprp1 that inhibit triglyceride and cholesterol absorption were confirmed to rise dramatically in the NAP-exposed group. The increased total cholesterol and CD68 levels were observed in the testis from the NAP-exposed group. Gpx5, serving as an antioxidant in sperm plasma, and Semg1, which contributes to sperm progressive motility, were both down-regulated. We concluded that the short-term exposure to NAP caused reproductive toxicity, primarily due to the inflammatory abnormality in the testis.